A study plan outlining a randomized control trial with two arms, conducted in parallel, to investigate the impact of a health education intervention on the utilization and implementation of insecticide-treated nets among pregnant women attending antenatal clinics - Onyinyechi, Opara Monica; Ismail, Suriani; Mohd Nazan, Ahmad Iqmer Nashriq (Universiti Putra Malaysia Press, 2024)
Introduction: Estimating the real extent of the health impact caused by malaria globally is essentially an educated estimation in the scientific realm. However, there is no denying that the most significant toll is observed in sub-Saharan Africa. Methods: This research will involve an intervention study utilizing a two-arm double-blind parallel randomized controlled trial, conducted in three stages. The initial stage will focus on creating a Health Belief Model (HBM) program. In the second stage, pregnant women will be enlisted, evaluated for baseline data, randomly assigned to two study arms, and monitored over a six-month period. The final phase will assess the influence of the intervention on the Health Belief Model (HBM) and share the results. Information will be gathered through a structured questionnaire incorporating validated instruments. The primary outcome will be the treatment effect assessed with the HBM Knowledge of malaria and ITNs use, attitude towards malaria and ITNs use, practices towards malaria and ITNs use, health seeking behaviour and health belief model factors, and data will be analyzed using SPSS, version 22 of the following analysis: Independent T-Test, Repeated Anova and (Gee) General Estimating Equation. Discussion: The research will add to the current understanding of care programs for pregnant women in hospitals in developing nations with limited existing literature. It will provide a broader perspective on the significance of measuring Health Belief Model (HBM) in intervention studies related to malaria and other infectious diseases in this specific context.